2008
DOI: 10.1002/pssa.200880457
|View full text |Cite
|
Sign up to set email alerts
|

Directional selectivity and ultra‐light‐trapping in solar cells

Abstract: Directional and energy selective optical surface structures attached to solar cells may result in both, enhancement or deterioration of photovoltaic performance of a solar cell. On the one hand, restricting the cell acceptance to the small incidence angle of direct and circumsolar irradiation enhances the maximum path length of the light in a solar cell with Lambertian surfaces even above the Yablonovitch limit (ultra-light-trapping). On the other hand, restrictions to small acceptance angles imply losses of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…Consequently, the surface textures used in present solar cells are believed to offer belowLambertian light trapping, with optical path length enhancements of around 10 [46]. It should be observed that the Lambertian Limit is not an upper limit; it can be superseded at some wavelengths through the use of diffraction gratings [47], angle-selective filters [48] and near-field absorption enhancement techniques [49]. However, in this work, we take an optical absorption enhancement of 50 to be optimistic and absorption enhancements of 10 to be realistic, and do not consider the wavelength dependence of the absorption enhancement.…”
Section: Absorption Enhancement Via Light Trappingmentioning
confidence: 97%
“…Consequently, the surface textures used in present solar cells are believed to offer belowLambertian light trapping, with optical path length enhancements of around 10 [46]. It should be observed that the Lambertian Limit is not an upper limit; it can be superseded at some wavelengths through the use of diffraction gratings [47], angle-selective filters [48] and near-field absorption enhancement techniques [49]. However, in this work, we take an optical absorption enhancement of 50 to be optimistic and absorption enhancements of 10 to be realistic, and do not consider the wavelength dependence of the absorption enhancement.…”
Section: Absorption Enhancement Via Light Trappingmentioning
confidence: 97%
“…Ulbrich and colleagues present a design for front-side photonic crystals which exploit directional selectivity to enhance performance [ 150 ]. The principle of this structure is to place a selective filter at the front of the solar cell over top of a randomized scattering layer.…”
Section: Front-side Photonic Crystalsmentioning
confidence: 99%
“…62 To calculate the absorptance, we assume a front surface reflectance R f = 0 and a back surface reflectance R b =1 as well as one Lambertian diffuser on top of the absorber layer. Then the absorptance follows as, [63][64][65] …”
Section: ͑11͒mentioning
confidence: 99%